Feeding behavior in Caribbean surgeonfishes varies across fish size, algal abundance, and habitat characteristics. (11th July 2019) - Duran, Alain; Adam, Thomas C.; Palma, Laura; Moreno, Shalimar; Collado‐Vides, Ligia; Burkepile, Deron E.
Abstract: Feeding behavior of coral reef fishes often determines their species‐specific ecological roles. We studied the two most common Caribbean surgeonfishes ( Acanthurus coeruleus and Acanthurus tractus ) to examine their species‐specific grazing rates and feeding preferences and how these differed with environmental context. We quantified the feeding activity of both surgeonfishes at four spur and groove reefs in the Florida Keys, USA, that varied in fish abundance, rugosity, algal community composition, and sediment loading. Overall, A. tractus fed twice as fast as A. coeruleus . Both species selected for turf algae but avoided feeding on turf algae that had become laden with sediment. Selectivity for upright macroalgae was more complex with A. tractus targeting Dictyota spp., while A. coeruleus avoided Dictyota spp . relative to the alga's abundance. Both species selected for epiphytes growing on other organisms such as macroalgae and sponges. However, several of these feeding patterns changed with ontogeny. For example, larger individuals of both species fed more frequently on long, sediment‐laden algal turf and less frequently on Dictyota spp. compared to smaller sized individuals. In addition, A. tractus also increased its preference for upright calcareous algae as they attained larger sizes. Overall, the disparity in feeding preferences of surgeonfishes likely indicates subtle differences in species‐specific ecological roles. Both A. coeruleus and A. tractus likely prevent development of turf algae and thus maintain algal communities in the early stages of succession. Additionally, A. tractus may also help reduce macroalgal abundance by targeting common macroalgal species.